Impact of Environmental Information Disclosure on Cost of Equity and Financial Performance in an Emerging Market: Evidence from Turkey - Atasel, Oğuz Yusuf; Güneysu, Yusuf; Ünal, Hüseyin (Ekonomika, 2020)
Financial instability, financial crises, and business frauds cause a loss of society confidence on firms. Similarly, the economic uncertainty increased as a result of the social problems, such as rapid consumption of natural resources, climate change, water scarcity, violation of human rights. For these reasons, the reliability and validity of the reports published by firms have been questioned. Firms make voluntary disclosures, such as environmental, social, sustainability, in order to overcome these problems and gain trust of investors. In this context, the purpose of this study is to explore the impact of information disclosure, including environmental disclosures, within the context of sustainability on the cost of equity (COE). At the same time, the study examines the effect of information disclosure on financial performance in terms of firm value and profitability. In doing so, the study employs BIST100 data of non-financial firms from 2010 to 2019, and uses panel regression models for Turkey. As a result, it was found that information disclosure negatively impacts the COE while positively affecting firm value and profitability.
Keywords: Environmental information disclosure; Sustainability report; Cost of equity; Firm value; Firm profitability